Efectos Biológicos e Impacto Ambiental de la Radiación No Ionizante Emitidas por las BTS con Sistemas de Comunicaciones Móviles 4G en la Ciudad de Loja - Medina Guadalima, David Andrés (2019)
The present thesis analyzes and evaluates the non-ionizing radiation emitted by 4G mobile phone base stations, specifically in CNT’s operator in the city of Loja. As a consequence of this spectral evaluation, the values of the electromagnetic fields are compared to conclude if it can cause health problems and also the environmental impact. Three chapters are presented: the first one is carrying out a review of the fundamental concepts about mobile phone technologies, emphasizing in its operation and net architecture. The second chapter, pretend to show a more in-depth approach to radiation in electric and telecommunications systems. It staring from the definitions about radiation and types of radiations, which allows to receives the differences between the two types of radiation and which of them is emitted by phone mobile stations. Furthermore, it presents some studies done to people exposed to non-ionizing radiation, possible health hazards, as well as the exposure reference limits to electromagnetic fields. The three chapter explains the reason why there are risk’s pollution of non- ionizing radiation in the environment. Subsequently, the electronic device to use is indicated, which should have a certification emitted by International Commission on Non-Ionizing Radiation Protection (ICNIRP). Then the methodology is raise, which is vital important when developing the measurement evaluation process according to the international norms and comply with the regulatory bodies of the country, ARCOTEL. The findings indicate that the values are below the maximum limits stablished by the International Commission on Non-Ionizing Radiation Protection (ICNIRP), the average of the non-ionizing radiation’s parameters through which was determined the moments where there is greater radiation’s emission are shown. Furthermore, graphs where the percentage comparison about radiation reference levels and zone schemes that reveal how the measurements were taken. This work contributes to the asserts that of base stations of CNT operator with 4G technology in the city of Loja whose radiation’s emissions is a type of non-ionizing, is not harmful to health and do not generate environmental impact. In addition, it was also found the compliance with the stipulated of current international and national norms.